The Role of Mid-Atlantic Ocean Data Portal in Supporting Ocean Planning - Lathrop, Richard G.; Odell, Jay; MacDonald, Tony; Vilacoba, Karl; Bognar, John; Trimble, Jim; Bruce, Chris; Crichton, Gwynn; Seminara, Drew; Herb, Jeanne; Campo, Matt (Frontiers in Marine Science, 2017)
The Mid-Atlantic Regional Council on the Ocean (MARCO) was established in 2009 to enhance the vitality of the region's ocean ecosystem and economy. One of MARCO’s first action items was the development of the Mid-Atlantic Ocean Data Portal to serve as an on-line platform to engage stakeholders across the region with the objective of improving their understanding of how ocean resources and places are being used, managed, and conserved. A key component is the Marine Planner, an interactive map-based visualization and decision support tool. These types of on-line tools are becoming increasingly popular means of putting essential data and state-of-the-art visualization technology into the hands of the agencies, industry, community leaders, and stakeholders engaged in ocean planning. However to be effective, the underlying geospatial data has to be seen as objective, comprehensive, up-to-date and regionally consistent. To meet this challenge, the portal utilizes a distributed network of web map services from credible and authoritative sources. Website analytics and feedback received during the review and comment period of the 2016 release of the Mid-Atlantic Ocean Action Plan confirm that the Data Portal is viewed as integral to this ocean planning process by the MidAtlantic Regional Planning Body and key stakeholders. While not all stakeholders may agree with specific planning decisions, there is broad based agreement on the need for better data and making access to that data widely available.